Ukuran Perusahaan Memoderasi Pengaruh CSR, Tax Avoidance, dan Sustainability Reporting terhadap Nilai Perusahaan - Reska Novia; Halmawati Halmawati (Universitas Negeri Padang, 2022)
The purpose of this research is to examine the effect of corporate social responsibility, tax avoidance, and sustainability reporting with size of company as a moderating variabel. The population of this research are companies engaged in extractive (agriculture sector and mining sector) and financial sectors listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period which total 180 companies. The sampling method was carried out by purposive sampling method, so 32 companies were obtained as research samples. The analytical method used moderated regression analysis. The results of this research indicate that 1) corporate social responsibility has positive effect on firm value 2) tax avoidance has negative effect on firm value 3) sustainability reporting does not effect on firm value 4) size of company support positive effect of corporate social responsibility on firm value 5) size of company support negative effect of tax avoidance on firm value 6) size of company does not effect of sustainability reporting on firm value. The contribution of the independent variable in explaining the dependent variable in the amount of 8,3%, while the remaining 91,7% explained by other variables outside the model.